GAMIFICATION: THE NEXT EVOLUTION OF EDUCATION (Proceedings of the International Conference on Future of Education, 2018)
Education is as effective as learning. Research has shown that learning when experienced is better. Experiencing learning through games can be better. This article inquires whether gamification of content improves learning. For administering this inquiry, a game is designed taking learning content from a course of geography in the curriculum of school students. Using this, findings from a preliminary experimental study conducted across 8-9 year old students of the school in question show that learning, in terms of being able to recall the topics understood, is better for the group that learnt through gamified content. Analysis of data through measures of central tendency across groups is indicative of this improvement. We present our game- based learning environment and findings in this context.
Keywords: Gamification; Game based learning; Gamification of Education; Evolution of education